A metasurface‐enabled wideband high‐gain dual‐circularly‐polarized Fabry‐Perot resonator antenna. Issue 10 (5th May 2020) - Huang, Ruimin; Wang, Zhenglong; Li, Guowei; Lin, Chengxiu; Ge, Yuehe; Pu, Jixiong
Abstract: This paper presents a wideband high‐gain dual‐circularly‐polarized (CP) antenna with a simple configuration. Instead of improving the gain using the dual‐CP element array, the Fabry‐Perot resonator antenna concept is applied in this work. By designing a dual‐linearly‐polarized Fabry‐Perot resonator antenna and a linear‐to‐circular polarization (LP‐CP) metasurface polarizer separately and combining them, a wideband high‐gain dual‐CP antenna can be achieved. Structural simplicity and less design difficulty are advantages of the antenna design. Experimental results validate the design concept. It exhibits 3‐dB axial‐ratio bandwidths of over 12% for both LHCP and RHCP performance, a high polarization isolation of over 25 dB, and peak gains of 12.78 dBi and 12.89 dBi for LHCP and RHCP radiations respectively.